2022
DOI: 10.1371/journal.pone.0273727
|View full text |Cite
|
Sign up to set email alerts
|

Are we leaving someone behind? A critical discourse analysis on the understanding of public participation among people with experiences of participatory research

Abstract: Participatory research (PR) is on the rise. In Spain, PR is scarce in the field of health, although there is an increasing interest in the matter. A comprehensive understanding of the meanings and practical implications of “public participation” is essential to promote participation in health research. The aim of the study is to explore the discursive positions on PR among individuals with experience in participatory processes in different areas and how this understanding translates into practice. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Of those, Ali et al discussed that it was hard to maintain the contact and interest of participants; Newman et al found difficulties with community involvement in the identification of priorities, which may not be uniform and could affect the selection process. According to the literature, power may remain concentrated in agents within academic settings, as well as economic and political institutions, whereas socially excluded individuals are powerless [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, Ali et al discussed that it was hard to maintain the contact and interest of participants; Newman et al found difficulties with community involvement in the identification of priorities, which may not be uniform and could affect the selection process. According to the literature, power may remain concentrated in agents within academic settings, as well as economic and political institutions, whereas socially excluded individuals are powerless [ 64 ].…”
Section: Discussionmentioning
confidence: 99%